DINAMIKA PERTUMBUHAN MANGROVE DAN HUBUNGAN SEDIMEN DI NIGERIA BARAT SELATAN - Ufuoma Akpovwovwo (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2020)
The mangrove ecosystem is not exempted from the fundamental interlinkages of components ensuring their functionality and development. Proper understanding of the interrelations between sediment parameters and their potential influence on mangrove growth is limited. This study examined mangrove structure across South western Nigeria, their growth dynamics, successional stage and relationship with the underlying sediments. Vegetation measurements and soil sampling (0-30cm) were carried out in one hundred quadrats of 20m by 20m. Sediments underwent laboratory analysis using standard procedures. Multiple regression was used to evaluate the relationship between the sediments and structural parameters at the 0.05 significance level. Ongoing degradation was detected, with evidence of selective harvesting targeted in the critical younger classes of <6cm, 6.1-9cm and 9.1-13cm. Phosphorus, magnesium, pH, salinity, sodium, silt and organic carbon were significant factors, contributing approximately 53 percent to the height. Electrical conductivity, organic carbon, salinity, total acidity, pH and silt were significant factors, contributing approximately 56 percent to the girth. The mangrove forests, though at a matured stage, are endangered. Sediment parameters, especially texture, have a significant influence on mangrove growth. Preparation of specialised sediment treatments for mangrove regrowth sites and also the setting up of conservation sites should be adopted.